FOLKLORIC DANCE IN CHILDREN EDUCATION: PEDAGOGICAL POSSIBILITIES THROUGH PHYSICAL EDUCATION (Fiep Bulletin - online, 2019)
The presente essay deals with the human cultural production from innumerable codes that embrace its life and thatleads them to the collectivity. In this context the body is perceived as an essential instrument in the process of socialization amongparticipants in cultural activities. Thus, this article aims to address the importance of Physical Education based on folk dances inearly childhood education, considering small children as a target audience, who have a playful profile and who still do not discernphysical activities as being athletic. However, we will talk about the practice of Physical Education as an important educationalresource among the children of the initial series, in the sense of promoting folkloric activities that bring dance in its content. Whenwe highlight folk activities as being important for physical activities, we also seek to value the cultures existing in our nationalterritory, as well as to deal with the cultures of the existing societies, which have a great deal to contribute to the dance activitiesthat are important to be exercised with children in the educational context. In this way, popular expression, dance folk, has theability to become an element of plural directions and senses that can lead to readings and re-readings of the human being andtheir cultural-pedagogical integration, collated under the aegis of body expressions. In this way, we demonstrate to elevate theelements of the folk dances as a facilitating practice for different pedagogical objectives, directed towards cultural, corporal andsocial education.
Keywords: The presente essay deals with the human cultural production from innumerable codes that embrace its life and that leads them to the collectivity. In this context the body is perceived as an essential instrument in the process of socialization among partic